PENGARUH MOTIVASI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRASFORMASIONAL (STUDI PADA GURU SD PNS UPT DINDIKBUD KECAMATAN TALUN KABUPATEN PEKALONGAN) (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research aims to understand how the influence of motivation on the performance of teachers , how the influence of professional competency on the performance of teachers , how theinfluence of leadership tranformasional on the performance of teachers , whether transformational leadership motivation moderating influence on the performance of teachers , and whethertransformational leadership moderating the influence of professional competency on the performance of teachers .The population in this research was of primary school teachers who arecivil servants of Dindikbud in Talun Pekalongan District , with proportional technique random sampling obtained samples from 134 people as respondents .Data analyzed by regression analystworship of idols. The results of the study can be concluded motivation have had a positive impact and significant impact on performance of teachers, professional competency have had a positiveimpact significant impact on performance of teachers, leadership transformational have had a positive impact and significant impact on performance of teachers, leadership transformationalmoderating influence motivation of the performance of teachers, and leadership transformational not moderating the influence of professional competency of the performance of teachers.Keywords: motivation , professional competency , transformational leadership and performance teacher.